A Hero's Journey in a German psychiatric hospital: A case study on the use of role method in individual drama therapy. Issue 1 (1st April 2016) - Klees, Simone
This article provides a case example of individual drama therapy in a psychiatric hospital in Germany. A case study on the use of the role method, and specifically the Hero's Journey, with a middle-aged, female diagnosed with personality and anxiety disorder is presented. The participant endorsed the utility of this approach in helping her experience relief and a sense of control over her presenting symptoms. Further research into the efficacy of the role method in individual drama therapy is needed in order to promote the use of such treatment within the context of the local mental health system.